Are brief interventions to increase physical activity cost-effective? A systematic review. Issue 7 (5th October 2015) - GC, Vijay; Wilson, Edward CF; Suhrcke, Marc; Hardeman, Wendy; Sutton, Stephen
Abstract : Objective: To determine whether brief interventions promoting physical activity are cost-effective in primary care or community settings. Design: Systematic review of economic evaluations. Methods and data sources: We searched MEDLINE, EMBASE, PsycINFO, CINAHL, EconLit, SPORTDiscus, PEDro, the Cochrane library, National Health Service Economic Evaluation Database and the Cost-Effectiveness Analysis Registry up to 20 August 2014. Web of Knowledge was used for cross-reference search. We included studies investigating the cost-effectiveness of brief interventions, as defined by National Institute for Health and Care Excellence, promoting physical activity in primary care or the community. Methodological quality was assessed using Drummond's checklist for economic evaluations. Data were extracted from individual studies fulfilling selection criteria using a standardised pro forma. Comparisons of cost-effectiveness and cost-utility ratios were made between studies. Results: Of 1840 identified publications, 13 studies fulfilled the inclusion criteria describing 14 brief interventions. Studies varied widely in the methods used, such as the perspective of economic analysis, intervention effects and outcome measures. The incremental cost of moving an inactive person to an active state, estimated for eight studies, ranged from £96 to £986. The cost-utility was estimated in nine studies compared with usual care and varied from £57 to £14 002 per quality-adjusted life year; dominant to £6500 per disability-adjusted life year; and £15 873 per life years gained. Conclusions: Brief interventions promoting physical activity in primary care and the community are likely to be inexpensive compared with usual care. Given the commonly accepted thresholds, they appear to be cost-effective on the whole, although there is notable variation between studies.